IMPLEMENTASI PERATURAN DAERAH NOMOR 3 TAHUN 2018 ATAS FENOMENA PENGEMIS DI KOTA PALU PERSPEKTIF FIKIH SIYASAH - Karmila S. Pontoh; Yuni Amelia (Qaumiyyah: Jurnal Hukum Tata Negara, 2022)
This study aims to understand and analyze the implementation of Regional Regulation Number 3 of 2018 concerning the Phenomenon of Beggars in Palu City from the Perspective of Fiqh Siyasah. This study uses a descriptive analysis method and then draws conclusions using a deductive mindset, namely the analysis taken by stating general provisions regarding Regional Regulations in handling beggars. Furthermore, these provisions are used to analyze the implementation of Regional Regulation Number 3 of 2018 based on the Siyasah Fiqh perspective. The results showed that the implementation of the Palu City regional regulation Number 3 of 2018 on the handling of beggars in the city. Based on the Government Regulation of the Republic of Indonesia Number 31 of 1980 Article 2 explains that the prevention of homeless and beggars includes preventive, repressive, rehabilitation, and social reintegration efforts. In the Siyasah Jurisprudence Review on the Implementation of the Palu City Regional Regulation Number 3 of 2018 the phenomenon of beggars does not conflict with the principles contained in siyasah fiqh. based on the principles of siyasa fiqh that are oriented towards benefit, avoiding elements of tyranny, the principle of justice and equality of rights, and based on the principle of deliberation. Abstrak Penelitian ini bertujuan untuk memahami dan menganalisis implementasi Peraturan Daerah Nomor 3 Tahun 2018 tentang Fenomena Pengemis di Kota Palu Perspektif Fikih Siyasah. Penelitian ini menggunakan metode analisis deskriptif kemudian diambil kesimpulan dengan menggunakan pola pikir deduktif yaitu analisa yang diambil dengan mengemukakan ketentuan secara umum tentang Peraturan Daerah dalam penanganan pengemis. Selanjutnya ketentuan tersebut digunakan untuk menganalisis implementasi Peraturan Daerah Nomor 3 Tahun 2018 berdasarkan perpektif Fikih Siyasah. Hasil penelitian menunjukkan Implementasi peraturan daerah Kota Palu Nomor 3 Tahun 2018 atas penanganan pengemis di kota Berdasarkan Peraturan Pemerintah Republik Indonesia Nomor 31 Tahun 1980 Pasal 2 menjelaskan bahwa penanggulangan gelandangan dan pengemis yang meliputi upaya-upaya preventif, represif, rehabilitasi, dan reintegrasi sosial. Dalam Tinjauan Fikih Siyasah Terhadap Implementasi Peraturan Daerah Kota Palu Nomor 3 Tahun 2018 atas fenomena pengemis tidak bertentangan dengan prinsip-prinsip yang ada dalam Fikih Siyasah. berdasarkan prinsip-prinsip Fikih Siyasah yang berorientasi pada kemaslahatan, menghindari unsur kedzaliman, prinsip keadilan dan persamaan hak, serta berdasarkan prinsip musyawarah.